Serviços ecossistêmicos e fragmentação da paisagem no parque estadual Mata do Pau-Ferro, Areia, Paraíba - Campos, Jean Oliveira (2022)
The Brazilian Atlantic Forest suffers intense degradation since colonization, which led its ecosystems to experience a steep fragmentation. The forest remaining provide fundamental ecosystem services for populations, even so, they run the risk of disappearing in the coming years due to the expansion of human activities in these areas. In the state of Paraíba, the Pau-Ferro Forest State Park in the municipality of Areia shelters one of the largest remaining Atlantic Forest in the state in the environment altitude swamp. Despite its importance, the protected area and its Buffer Zone are permeated by conflicts that affect its conservation, part of them related to the advance of farming over forest perimeters. In light of the above, the research has the general purpose of analyzing the vegetation fragmentation and mapping the main services of provision, regulation, and maintenance provided through the fragments of native forest contained in the Pau-Ferro Forest State Park and in its Buffer Zone. For the fragmentation analysis, were used landscape metrics, they were executed through the V-LATE 2.0 extension, in the ArcGIS 10.2 software. The provision services mapping, on its part, was based on the matrix method and included the application of questionnaires and field visits. The ecosystem services of regulation and maintenance, in its turn, were mapped through the integration of environmental variables, thus, the carbon sequestration service was mapped through the CO2flux index, whereas, the erosion control mapping was based on the Universal Soil Loss Equation (USLE). The Buffer Zone presents a notorious fragmentation of native forest vegetation, which leads to the manifestation of the following conditions: predominance of small fragments, rounded shapes, low medium sizes, steep structural connectivity, and high vulnerability to the edge effects. With regard to provision services, supply capacities vary between very high and not relevant. The highest supply was recorded for fibers and materials from wild plants, while the lowest was observed for nutrition from wild animals. Then, the carbon sequestration pronounced capacities of similar supply to those observed in provision services, varying between high and not relevant, however, small and large fragments presented close potentials for the ecosystem service provision. Finally, in the erosion control service, were manifested supply capacities that were varying between very high and very low. The results presented converge to highlight that the native forest vegetation of the Pau-Ferro Forest State Park and its Buffer Zone constitutes important areas for providing ecosystem services to local communities and the society as a whole, and the advance of fragmentation may conduct the landscape to ecological conditions more unfavorable to services. In these terms, the mapping allowed increasing knowledge about the areas of provision and supplies, contributing to identifying conflicts and strategies for resolving them. Furthermore, the information can be used as a subsidy for the elaboration of public actions aimed at protecting forest fragments and maintaining the supply of ecosystem services.